COVID-19 in Baghdad, Iraq: adaptive and emotional findings in a household cluster survey - Lafta, Riyadh; Al-Shatari, Sahar; Mary, Meighan; Burnham, Gilbert (Frontiers in Public Health, 2023)
Purpose. The objective of this study was to assess the impact of COVID-19 infection on households in Baghdad, Iraq.Methods. A cross-sectional household survey was conducted in early 2022; 41 clusters were selected proportional to population size from the districts of Baghdad governorate. Households were randomly selected for inclusion. The head of household or senior female member present was interviewed to obtain a listing of COVID-19 infections, deaths, and vaccinations among members in the household and to understand if social and economic changes occurring during the pandemic. All analyses incorporated the complex survey design and sample weights for clustering.Findings. The findings revealed that there were 1,464 cases of COVID-19 (37.1%) and 34 reported fatalities among the 927 households enrolled in this study One or more COVID-19 immunizations were received by 50.9% of household members. Preventive measures against COVID-19 were widely reported being practiced but were not more commonly reported in households having reported a clinical case of infection. While some households where infections had occurred stated their household expenses were increased, overall, infections were not associated with significantly increased household costs. In households where COVID-19 had occurred, senior members reported a substantial increase in emotional and psychological problems compared with uninfected households.Implications. COVID-19 deaths were rare though infections common, suggesting an effect from vaccination and other efforts. The household economic implications were minimal in houses with and without COVID-19 infected members. The mental health consequences of the infection on affected and unaffected populations alike. It is conceivable that the fear and uncertainty generated by the pandemic had an effect on senior household members which was out of keeping with the other effects in the households sampled. This suggests that there may be persisting needs for mental health services for a protracted period to manage the consequence of mental health needs arising from the pandemic.